If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-20=-4x-6x=
We move all terms to the left:
-20-(-4x-6x)=0
We add all the numbers together, and all the variables
-(-10x)-20=0
We get rid of parentheses
10x-20=0
We move all terms containing x to the left, all other terms to the right
10x=20
x=20/10
x=2
| 10(4g-12)=24 | | 5(u-6)-7u=-12 | | X-14=-4x+26 | | -124=6(5-5x)+8x | | (x-3)^2+16=100 | | X2=6x-9 | | 6-4(7-8x)=0 | | -11f=7(-2f)+5 | | 8p=2+7p | | -5x-12=8-x | | 80=-20(12)+b | | 3-6(2x+7)=5 | | x-8=33/x | | -9=2(x+6)-5x | | 20=c+18 | | 102=-6(2-3x) | | 5/3(8x-3)=4 | | 102=-6(2-3x | | 1/5(3x+1/2=) | | 2/3=1/2-x/6 | | 5t|6=3t|7 | | 4x=5=4x-2 | | 12c+35)-(5c-11)=-2 | | -5n-36=-4(7-3n)-8 | | 5x-1=7-2x | | 2x+12=x+1 | | 6x-9-5∙(2x-3)=14-2x+6∙(2-x) | | 4x-2(3x-9)-11=2 | | {13k-53}/{2}-5=2k | | 17=u/3+8 | | b/6=1 | | 5−2j=3 |